RESEARCH ON MULTI-FIELD COUPLING CHARACTERISTICS OF FLUID, THERMAL AND SOLID IN ROTARY EXCITATION VALVE (MT) - LU ShengDong; WANG SiHan; ZHAO ZiYan; ZHAO GuoChao; WANG Hui (Jixie qiangdu)
The rotary excitation valve is one of the key components for the high-frequency and high-pressure electro-hydraulic excitation system, and its dynamic characteristics directly affect the performance of the entire excitation system.In order to study the dynamic characteristics of the rotary excitation valve under the coupling effect of Fluid-Thermal-Solid multi-field. First, the flow field of the rotary excitation valve was dynamically simulated by the sliding grid method through Fluent simulation, and the simulation results were verified by the measured flow rate of the rotary excitation valve. Then, the Fluid-Thermal-Solid multi-field coupling simulation of the rotary excitation valve was performed by using ANSYS. The thermal characteristics and thermal deformation laws of the rotary excitation valve was studied when the pressure difference between inlet and outlet ΔP are 5 MPa, 10 MPa, 15 MPa and the oil temperature are 20℃, 40℃, 60℃ respectively. The research results show that the internal flow field and temperature field of the rotary vibration valve are not uniformly distributed. The temperature of fluid near the valve core and the wall of valve body is higher, and the center temperature is lower.Due to the impact of the fluid at the outlet of rotary excitation valve, a local high temperature will be generated, resulting in thermal deformation of the valve core groove and the valve body outlet port.When the pressure difference between inlet and outlet at 15 MPa, the thermal deformation is 3.789 4 μm, and the oil inlet temperature at 60℃, the thermal deformation is 7.701 7 μm. Therefore, choosing the pressure difference between inlet and outlet and oil temperature is beneficial to the operational characteristics for rotary excitation valve. The theoretical data for the structural design and optimization of the rotary excitation valve are provided.